Penerapan Metode Design Thinking dan Agile Development Pembangunan Aplikasi Marketplace “Hijab” - Anis Lelitasari; Reza Ilyasa; Rangga Gading Satria; Nurdin Effendi; Muhammad Qaddasa (Journal of Information System Research (JOSH), 2023)
The development of information technology is growing increasingly rapidly, many activities have been helped by technology, one of which is the process of buying and selling transactions. At this time people prefer to make buying and selling transactions online, this is because it can facilitate transactions such as seeing the details of the goods, the transaction process is easier and more efficient. Currently, hijab producers in the cikarang area who have a large market in work channeling institutions (LPK) to Japan market merchandise to interns directly or manually not utilizing technology. The current manual transaction process has many disadvantages including the need for a place, time for the buying and selling process, the process of recording transactions often makes mistakes. Things like this cause problems both from the seller or buyer side. From the problems that occur, a mobile marketplace application system "Hijab" will be made using the Design Thinking Method and Agile Development. The results of this study with the "Hijab" application can help hijab producers and LPK interns in the transaction process. This application can help introduce hijab products owned by hijab producers in the Cikarang area with this application product details are easy to convey because they are listed on the application, the transaction process will also be more neatly recorded. From the buyer / intern side, it will also be more helpful, namely being able to make transactions anytime and anywhere in the application.